Pembangunan Aplikasi Reka Bentuk Kek Menggunakan Pendekatan Realiti Terimbuh - Selamat, Nur Farah Syakila; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2021)
Social media is a medium on the Internet that allows users to represent themselves to interact or communicate with other users virtually. Hence, many users nowadays prefer to order cakes online but there are less satisfactory cake results because they are only guided by pictures instead of seeing the cake directly. Therefore, the Cake Design app Using Augmented Reality was developed to help users order cakes and able to view existing cakes in 3D AR. The objective of this project is to design a cake design application using a 3D perspective method developed based on mobile devices and to test the functionality on the target users by using an augmented reality perspective. The methodology used is the Agile model which has five phases which are planning, analysis, design, development, and testing because this model is suitable for a short project development period and does not require large cost. The main software in developing this application is Unity and developed with AR technology using Vuforia software. The results obtained because of the user acceptance test obtained are as much as 87.65% based on the usability measuring system (SUS). In conclusion, this application was successfully developed and achieved the objectives and goals that have been set. In conclusion, this application successfully develops and reach the objective and target.